How SARS-CoV-2 Delta Variant Was Curbed in Japan. Will Omicron Replace It? - Tikhonov D.G. (Siberian Research, 2021)
Сurbing the SARS-CoV-2 Delta variant in Japan has probably initiated extinction of the Delta variant and the pandemic. Whether Omicron will replace Delta has been unknown so far. In case of Spanish flu, mass mortality reached an end two years later, although up to 2% of the population died in some villages at the Spanish flu outbreak in Yakutia in 1925 [23]. If Omicron replaces Delta, COVID-19 may probably turn into a seasonal infection, provided that the majority of the world population gets vaccinated or get sick.